A STUDY OF ATTITUDE OF AMRAVATI UNIVERSITY EMPLOYEES TOWARDS PHYSICAL FITNESS (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
The objective of this study was to examine the attitude of Amravati university employees towards physical fitness. A sample of 100 employees from administrative and academic department was selected by quota sample. An attitude scale to measure physical fitness was used as a tool for data collection. Mean, S. C. and t-Test was used to analyse the data. Results indicate that more positive employees working in Amravati university have attitude towards physical fitness. In addition academic employees rave more positive attitude towards physical fitness in comparison ::administrative employees. Furthermore the male employees has more positive attitude towards physical fitness in comparison to female employees.Getting moving is a challenge because today physical activity is less a part of our daily lives. There are fewer jobs that require physical exertion. We have become a mechanical mobile society, relying on machines rather than muscles to get around. In addition, we have become a nation of observers with more people spending their leisure time pursuing just that leisure consequently. statistics shows that obesity and overweight, the problem that comes with high blood pressure, diabetes and cardiac arrest etc. are on the rise. But statistics also shows that preventive medicine pay off, so one should not weight until his/her doctor gives an ultimatum. Hence everyone must take the initiative step to get active.The world's greatest thinkers have stressed importance of physical fitness in living a productive meaningful life. The Greek philosopher Aristotle stated. "The body is the Temple of the soul and to reach harmony of body, mind and spirit, the body must be physically fit".